Creative Hub as a Creative Space for Young People of Palu City With Plowright Pattern-Based Design Method - Andi Faidilah; Fuad Zubaidi; Lilies Handayani (LPPM Universitas Tadulako, 2023)
This res earch is motivated by the increas e in the creative indus try s ector in Palu City, es pecially in the craft, film and performing arts s ubs ectors and als o the adjus tment of s pace for the public in the new normal era so that the urgency of the need for s paces that can facilitate creative activities , es pecially during this pandemic, needs to be provided, es pecially in the Palu City area s o that the title rais ed in the form of